Black flies and Onchocerciasis: Knowledge, attitude and practices among inhabitants of Alabameta, Osun State, Southwestern, Nigeria - Lateef O. Busari; Monsuru Adebayo Adeleke; Olabanji A. Surakat; Akeem A. Akindele; Kamilu Ayo Fasasi; Olusola Ojurongbe (Public Library of Science (PLoS), 2022)
Background and objectives This study reports knowledge of residents of Alabameta community, Osun State, Nigeria on the bioecology and socio-economic burden of black flies and onchocerciasis. Methods Using structured questionnaires and Focus Group Discussion (FGD), a total of 150 community respondents participated in the study. Results The knowledge of the residents on the existence of black flies in the community was significant (p<0.05) as all the 150 respondents confirmed the presence of black flies with the local name 'Amukuru' i.e causing itching. However, their lack of knowledge of the flies breeding site (104) (69%), prevention (134) (89%), cause (132) (88%), and treatment (133) (89%) of onchocerciasis was profound. Majority 147(98%) of the respondents reported that flies bite more in the wet season as against dry season 3(2%) and have a higher affinity (124) (82%) for biting the leg than any other part of the body. A larger percentage (89%) of the respondents are unaware of any medication for the treatment of onchocerciasis while 11% are aware. There had been no sensitization on onchocerciasis according to 89% of the respondents. Conclusion Due to lack of resident's knowledge on black flies bioecology which may continuously expose them to the bite of the flies and ultimately infection, it is paramount that the Osun State government and the NTD implementing partner map out new public health education strategies during routine Mass Administration of Medicines with Ivermectin with a view to preventing onchocerciasis infection as well as man-vector contact. Author summary The public health menace of parasites and their vectors is an issue of global public health concern. Black flies, the vector that transmit the dreadful parasite Onchocerca volvulus to its human host where it causes the debilitating disease, onchocerciasis, is a neglected tropical disease (NTD) with its greatest burden in sub-Saharan Africa. Nigeria is an endemic country for onchocerciasis. Despite efforts by health agencies globally in eradicating the disease through public health awareness, chemotherapy through community directed treatment with ivermectin (CDTI) and so on, it appears that inhabitants of Alabameta community, Osun State, southwestern, Nigeria are unaware of the bioecology of the vector as well as the public health implication of the disease according to the present study. Therefore, there is the urgent need for the government at the state and federal levels as well as health agencies to improve on public health awareness of the disease with a view to curbing exposure of residents and ultimately disease eradication.